Significance of the Boston Cognitive Assessment in patients with chronic post-stroke cognitive impairment - Yin, Xiao; Zhu, Haiying; Ji, Panpan; Wu, Beixuan; Zhang, Yi (Frontiers in Neurology, 2025)
BackgroundThe Boston Cognitive Assessment (BoCA) is an online, self-administered, remote cognitive screening tool for the early detection and long-term monitoring of health changes in the brain of aging populations. This study aimed to evaluate the reliability and validity of the Mandarin version of the BoCA in Chinese patients with stroke, thereby providing a reference for important clinical applications.MethodsThis study included 120 patients with chronic stroke and 120 healthy controls. All participants completed the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Mandarin versions of the BoCA. Assessments were spaced a minimum of 60 min apart. For the test–retest reliability analysis, 120 patients with stroke were retested on the BoCA after 1 week. The receiver operating characteristic (ROC) curves were generated to assess diagnostic performance.ResultsAmong the stroke group, the BoCA showed appreciable internal consistency (Cronbach’s α = 0.808) and significant test–retest reliability (intraclass correlation coefficient, ICC = 0.895, p < 0.001). The BoCA subscales demonstrated moderate-to-strong correlations with the total score (r = 0.546–0.770), supporting adequate content validity. The BoCA total scores were strongly correlated with the MMSE (r = 0.829, p < 0.001) and MoCA (r = 0.848, p < 0.001) scores, demonstrating adequate criterion-related validity. Exploratory factor analysis (EFA) of the BoCA tasks revealed one robust factor accounting for a plurality (i.e., 46.9%) of the total variance, indicating sufficient construct validity. An ROC analysis revealed comparable diagnostic performance for the BoCA (area under the curve, AUC = 0.823), MMSE (AUC = 0.836), and MoCA (AUC = 0.818). A BoCA score of 23.5 distinguished the stroke group from the control group with 81.7% sensitivity and 69.2% specificity.ConclusionThe Mandarin version of the BoCA exhibits significant reliability and validity and functions effectively as a supplementary measure for cognitive assessment in stroke survivors.